Meningoencephalomyelitis Caused by Brucella canis: A Case Report and Literature Review - Ishihara, Masaki; Abe, Satoshi; Imaoka, Koichi; Nakagawa, Tomonori; Kadota, Katsuhiko; Oguro, Hiroaki; Nakajima, Hideto; Yamaguchi, Shuhei; Nagai, Atsushi (Internal Medicine, 2024)
Human brucellosis, one of the most common zoonoses worldwide, is rare in Japan. Brucella canis is the specific pathogen of human brucellosis carried by dogs. According to an epidemiological study of B. canis infection in Japan, B. canis is the specific pathogen of human brucellosis in dogs. We herein report a rare case of meningoencephalomyelitis caused by B. canis in a 68-year-old Japanese man. Neurobrucellosis was diagnosed based on a serum tube agglutination test and abnormal cerebrospinal fluid findings. The patient was started on targeted treatment with a combination of doxycycline and streptomycin. Although extremely rare, neurobrucellosis should be considered in patients with a fever of unknown origin and unexplained neurological symptoms.